Altered GABA Concentration in Brain Motor Area Is Associated with the Severity of Motor Disabilities in Individuals with Autism Spectrum Disorder. - Umesawa, Yumi; Matsushima, Kanae; Atsumi, Takeshi; Kato, Toshihiro; Fukatsu, Reiko; Wada, Makoto; Ide, Masakazu (Journal of Autism & Developmental Disorders, 2020)
Several motor disabilities accompanied with autism spectrum disorder (ASD) are widely known despite limited reports of underlying neural mechanisms. Gamma-aminobutyric acid (GABA) levels in the motor-related cortical areas modulate several motor performances in healthy participants. We hypothesized that abnormal GABA concentrations in the primary motor area (M1) and supplementary motor area (SMA) associate with different motor difficulties for ASD adolescents/adults. We found that increased GABA concentrations in M1 measured using 1H-magnetic resonance spectroscopy exhibited lower motor performance in tasks requiring increased muscle strength while lower GABA concentrations in SMA were associated with lower scores in tests measuring body coordination. The degrees of neural inhibition in the M1 and SMA regions would contribute to different dimensions of motor disabilities in autism.